1999
DOI: 10.1046/j.1365-3040.1999.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air pollutants on proton and sucrose transport at the plasma membrane of Ricinus communis

Abstract: The effects of the air pollutants O 3 , SO 2 and NO 2 on aspects of sucrose/proton cotransport across the plasma membrane of Ricinus communis plants have been investigated. The H + -ATPase hydrolytic activity in cotyledon plasma membrane vesicles purified by phase partitioning showed small stimulations by Na 2 SO 3 or NaNO 3 added separately or together to the assay medium. ATPase activity from plants pretreated by fumigation with SO 2 or O 3 also showed an increase, the effect of O 3 being quite marked. Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, detrimental physiological responses including decreased photosynthesis (Saxe 1986), effects on plasma membranes (Russell et al 1999) and plant water-use efficiency (Siegwolf et al 2001) have been reported coincident with leaf fumigation with reactive N.…”
Section: Phytotoxicity Versus Airborne Nutritionmentioning
confidence: 99%
“…However, detrimental physiological responses including decreased photosynthesis (Saxe 1986), effects on plasma membranes (Russell et al 1999) and plant water-use efficiency (Siegwolf et al 2001) have been reported coincident with leaf fumigation with reactive N.…”
Section: Phytotoxicity Versus Airborne Nutritionmentioning
confidence: 99%